Giant dentigerous cyst of maxillary sinus associated with impacted maxillary canine - Rimbawan, P. P. G. Krisna Bayu Pramana; Windhu Saputra, I. Putu Gede; Natasha Roosseno, Ratna Rayeni (International Journal of Research in Medical Sciences, 2019)
Dentigerous cyst is a cyst that encapsulates enamel of the unerupted tooth, thus causing the tooth become unable to complete the eruption process. This cyst is defined as a developmental cyst as it generally occurs in first until the third decades of life. Dentigerous cyst commonly affect the mandibular area of the teeth. This article describes the case of a young patient with dentigerous cyst which affect maxillary canine. A 6-year-old girl was admitted to Plastic Reconstructive and Aesthetic Surgery Clinic at Mangusada Hospital Bali with facial asymmetry on her right cheek, noticed since the past one week. She got some medicines from the general physician, but there was no improvement. From the CT scan, we found a solitary mass on the size of 3 x 3.2 x 3.6 cm on the right maxillary area. Enucleation was done and the Caldwell-Luc approach was performed under general anesthesia. The cyst revealed to have an ectopic maxillary canine inside. The cyst and ectopic tooth were extracted from the pathological site and the incisional specimens were sent for histopathological examination. The result revealed a cyst lined by non-keratinized stratified squamous epithelium without any malignancy. She had antibiotics therapy post-surgery, and her symptoms were resolved within a week. In one month follow up, there was no sign of recurrence.